The characteristics of a Linear Joule Engine Generator operating on a dry friction principle. (1st March 2019) - Ngwaka, Ugochukwu; Jia, Boru; Lawrence, Christopher; Wu, Dawei; Smallbone, Andrew; Roskilly, Anthony Paul
Highlights: A new friction force model for a novel Linear Joule Engine Generator (LJEG) prototype is presented. Existing numerical friction force models are compared with experimental results. The relationship between friction and the LJEG dynamics are shown. Abstract: In this paper, the friction characteristics of a novel Linear Joule Engine Generator operating on dry friction mechanism is presented. A numerical model of the friction forces is represented through the development of a dry friction force model integrated into a mass-spring-damper system with viscous damping and spring constant to emulate compressor and expander operating pressures. Experimental results from a Linear Joule Engine Generator prototype are compared with the numerical simulation results predicted by the proposed friction model and other reported friction models identified from the wider engineering literature. Finally, the relationship between electric generator load and friction power of Linear Joule Engine Generator is established.